2009
DOI: 10.1038/clpt.2009.217
|View full text |Cite
|
Sign up to set email alerts
|

A Dosing/Cross-Development Study of the Multikinase Inhibitor Sorafenib in Patients With Pulmonary Arterial Hypertension

Abstract: Pulmonary arterial hypertension (PAH) and cancer share elements of pathophysiology. This provides an opportunity for the cross-development of anticancer agents that can be used in improving PAH care. The adaptation of new drugs across these disease populations warrants a structured approach. This study was a 16-week, phase Ib, single-center, open-label trial of the multikinase/angiogenesis inhibitor sorafenib. In order to assess the safety of sorafenib in PAH, patients with advanced but stable disease on paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(50 citation statements)
references
References 44 publications
1
47
0
1
Order By: Relevance
“…have observed a decrease in sorafenib exposure over a prolonged time; (ii) Hornecker et al 23. have recommended fractionated dosing to overcome saturable absorption; and (iii) Gomberg‐Maitland et al 38. recommended a dose of 200 mg b.i.d.…”
Section: Discussionmentioning
confidence: 99%
“…have observed a decrease in sorafenib exposure over a prolonged time; (ii) Hornecker et al 23. have recommended fractionated dosing to overcome saturable absorption; and (iii) Gomberg‐Maitland et al 38. recommended a dose of 200 mg b.i.d.…”
Section: Discussionmentioning
confidence: 99%
“…These are crucial aspects for further research, particularly because broadspectrum tyrosine kinase inhibition may have pleiotropic effects on the cardiopulmonary system. Sorafenib, for instance, had detrimental effects on cardiac output in patients with PAH, 36 and dasatinib has been identified as a potential cause of PAH. 37 In conclusion, this study provides evidence that imatinib, as the first representative of a new class of drugs for the treatment of PAH, improves exercise capacity and hemodynamics in patients with advanced PAH who remain symptomatic on at least 2 drugs of the currently available 3 drug classes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in animal models of PAH showed that treatment with sorafenib resulted in improvements in haemodynamic parameters and attenuation of pulmonary hypertension [91], and prevention of pulmonary remodelling and improvement in cardiac and pulmonary function [60]. In a preliminary dosing study, 12 patients with advanced but stable PAH on parenteral prostanoids (with or without oral sildenafil) were initiated on 200 mg sorafenib daily (the lowest active dosage administered to cancer patients) with dose escalations to a final dosage of 400 mg twice daily [92]. Sorafenib was well tolerated at 200 mg twice daily, and is currently under investigation in a phase I safety and tolerability study in patients with PAH already on existing therapy with a prostacyclin with or without sildenafil [93].…”
Section: Terguridementioning
confidence: 99%